Peran Profit Perusahaan Sektor Industri Barang Konsumsi dalam Mendukung Penghindaran Pajak (Tax Avoidance) di Indonesia - Shintia Apriliana; Amalia Nur Chasanah (Universitas Nusantara PGRI Kediri, 2024)
The obligation to pay taxes has become very important as taxes contribute significantly to state revenue. This research aims to determine the influence of profitability, leverage, and company size on tax avoidance. The study was conducted in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (BEI) during the period 2018-2022, with a population of 88 companies. The purposive sampling technique was used to select the sample, resulting in a research sample of 26 companies. Using predetermined criteria, the purposive sampling method was employed in the sample selection. A total of 130 metrics from 26 different companies were collected over five years. Descriptive statistical analysis included tests for normality, heteroskedasticity, autocorrelation, multiple regression tests, coefficient of determination tests, T-tests, and F-tests as part of the research analysis method. This procedure utilized SPSS Statistics 24. From the research results, it was found that tax profitability hasn’t effect on tax avoidance, while leverage and company size have an impact on tax avoidance.